Helium irradiation of Y2O3-Fe bilayer system. (15th March 2019) - Mairov, A.; Frazer, D.; Hosemann, P.; Sridharan, K.
Abstract: Y2 O3 /Fe bilayer systems and associated interfaces with different crystallographic orientations were implanted with helium. High resolution scanning transmission electron microscopy (HRSTEM) analysis showed that implanted helium formed larger sized bubbles at the interface than within the individual film layers. The bubbles at the interface were located on the oxide side of the interface and only "wetted" a small area of the interface. In contrast, bubbles nucleating at grain boundaries within the iron layer were observed to symmetrically form across the grain boundaries, suggesting remarkable differences in helium bubble nucleation between metal/oxide interfaces and grain boundaries in metals. Graphical abstract: Unlabelled Image